Plan de negocios para la creación de una empresa de pañales ecológicos en Bogotá (2021)
The main objective of this business plan is to determine the viability of creating an ecological diaper company in the city of Bogotá, Colombia. From the perspective of innovation, this project has two fundamental axes, in addition to the commercial and economic objective, it is intended to generate a social impact by raising awareness around the issue of the use of disposable diapers and their impact on the environment.